A magnetoelastic biosensor based on E2 glycoprotein for wireless detection of classical swine fever virus E2 antibody. Issue 1 (December 2017) - Guo, Xing; Sang, Shengbo; Guo, Jinyu; Jian, Aoqun; Duan, Qianqian; Ji, Jianlong; Zhang, Qiang; Zhang, Wendong
Abstract A wireless magnetoelastic (ME) biosensor immobilized with E2 glycoprotein was first developed to detect classical swine fever virus (CSFV) E2 antibody. The detection principle is that a sandwich complex of CSFV E2 – rabbit anti-CSFV E2 antibody – alkaline phosphatase (AP) conjugated goat anti-rabbit IgG formed on the ME sensor surface, with biocatalytic precipitation used to amplify the mass change of antigen–antibody specific binding reaction, induces a significant change in resonance frequency of the biosensor. Due to its magnetostrictive feature, the resonance vibrations and resonance frequency can be actuated and wirelessly monitored through magnetic fields. The experimental results show that resonance frequency shift increases with the augmentation of the CSFV E2 antibody concentration. Scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS) and fluorescence microscopy analysis proved that the modification and detection process were successful. The biosensor shows a linear response to the logarithm of CSFV E2 antibody concentrations ranging from 5 ng/mL to 10 μg/mL, with a detection limit (LOD) of 2.466 ng/mL and the sensitivity of 56.2 Hz/μg·mL−1 . The study provides a low-cost yet highly-sensitive and wireless method for selective detection of CSFV E2 antibody.